UNI/TR 11950:2024 – Safety and health in the use of occupational exoskeletons intended to facilitate work activities: L. Monica | INAIL, Department of Technological Innovation and Safety of Plants, Products, and Anthropogenic Settlements, Italy (Giornale Italiano di Medicina del Lavoro ed Ergonomia, 2026)
Introduction. Work-related musculoskeletal disorders due to biomechanical overload are associated with physical risk factors related to manual handling activities and activities that require maintaining fixed and awkward postures for prolonged periods of time. Wearable devices like exoskeletons are presented as a useful solution to reduce or mitigate the risks of biomechanical overload, but this requires proper implementation in workplaces as a precondition to avoid potential risks associated with their use.Objectives. The presentation aims to outline the contents of the technical report UNI/TR 11950:2024 – Safety and health in the use of occupational exoskeletons designed to facilitate work activities. The document, developed by the UNI/CT 042/SC 01/GL 16 working group “Safety and Health of Wearable Devices to Facilitate Work Activities”, was published in April 2024.Methods. The traditional approach to mitigating the risks of biomechanical overload involves adopting preventive measures to eliminate or at least reduce the potential for harm, such as proper workplace design, proper management of work activities, and appropriate selection of work equipment used by the worker. In cases where these preventive measures are not effective in mitigating the risk of biomechanical overload, the use of exoskeletons is being introduced in some production settings. It is necessary to assess the contribution of these devices and, above all, what their contribution to risk reduction can be, what residual risks will remain, and what risks, on the other hand, might be introduced by their use in different production contexts.Results and Conclusions. UNI/TR 11950 delves into the state of the art of occupational exoskeletons and aims to:- provide guidance on the correct terminology and definitions to be adopted in the field of occupational exoskeletons;- identify and describe the different types of exoskeletons currently developed and in use in work environments (with particular reference to active and passive ones);- illustrate the general principles of exoskeleton design and construction;- represent the work sectors where exoskeletons can be applied;Defining a common terminology and classification for these devices, specifying their fields and limitations of application, as well as their functional, design, and construction characteristics, is essential to initiate their correct and informed use. The technical report is an important first contribution to technological development in this sector.